Pengaruh Budaya Organisasi Dan Lingkungan Kerja Terhadap Komitmen Organisasi Melalui Kepuasan Kerja Di PT Solusindo Kreasi Jayatech - Kevern Brox Arsenio (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
The purpose of this study is to describe the results of an analysis of the influence of organizational culture and work environment on organizational commitment through satisfaction. The research method uses a quantitative approach, with sampling or data sources using the Slovin formula with an error rate of 10% as a processing tool to measure sample size because it is known that the population is more than 100 respondents. Instrument test using validity test and reliability test. While testing the hypothesis using the R square test, path analysis test, model fit test. The results of research on PT Solusindo Kreasi Jayatech employees using the SmartPLS 3 calculator and with quantitative research methods, it can be seen that organizational culture has no positive and significant effect on organizational warnings, organizational culture has a positive and significant effect on job satisfaction, work environment has a positive and significant effect on job satisfaction, the work environment has a positive and significant effect on organizational commitment, and job satisfaction has a positive and significant effect on organizational commitment.